Monsters from Myth, and Quests for a Scientific Rationale, Or, a Science Journalist’s Take on Mythological Animals. An Exploration of Matt Kaplan’s The Science of Monsters, with a Foray into Aetiologies and Cultural Uses of Medusa - Nissan, Ephraim (Amaltea. Revista de Mitocrítica, 2018)
We consider some of the chapters in Matt Kaplan’s The Science of Monsters and his rationalising conjectures (some of them rooted in hypotheses by Adrienne Mayor), and discuss or provide supplementary data, including concerning occurrence in modern art or literature.